2005
DOI: 10.1212/01.wnl.0000182293.34015.a9
|View full text |Cite
|
Sign up to set email alerts
|

Extensive brain calcification and dementia in postsurgical hypoparathyroidism

Abstract: Abstract-The authors report four patients with a syndrome of painless bilateral isolated phrenic neuropathy. Electrophysiologic testing demonstrated active denervation restricted to the diaphragm. Long-term recovery was poor. The authors conclude that bilateral isolated phrenic neuropathy is a cause of painless diaphragmatic paralysis distinguishable from immune brachial plexus neuropathy and other neuromuscular disorders with similar clinical presentation. Bilateral phrenic neuropathy is a rare cause of unexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The phenomenology and severity of the neurological involvement deserves some further comment. Delirium and cognitive decline are manifestations of HP and PHP, being usually associated and maybe pathophysiologically related to the presence of intracranial calcification (Adorni et al ; Baptista et al ; El Otmani et al ; Kowdley et al ; Nicolai & Lazzarino ; Roca et al ). Hypocalcemia seems to be a key factor for calcifications as well as for common neurological symptoms like tetany, muscle cramping and seizures, which usually respond quickly to calcium replacement (Friedman et al ; Fujita ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenology and severity of the neurological involvement deserves some further comment. Delirium and cognitive decline are manifestations of HP and PHP, being usually associated and maybe pathophysiologically related to the presence of intracranial calcification (Adorni et al ; Baptista et al ; El Otmani et al ; Kowdley et al ; Nicolai & Lazzarino ; Roca et al ). Hypocalcemia seems to be a key factor for calcifications as well as for common neurological symptoms like tetany, muscle cramping and seizures, which usually respond quickly to calcium replacement (Friedman et al ; Fujita ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic HP and, more rarely, PHP are associated with central neurologic manifestations like epileptic seizures and extrapyramidal signs (Bhadada et al ; Guberman & Jaworski ; Mitchell et al ). The classical radiological finding is calcification of the basal ganglia (Faissolle et al ; Goswami et al ; Kahloul et al ) and encephalopathy (Gupta et al ; Handa et al ; Oechsner et al ) or rapidly progressive dementia (Adorni et al ; Mateo & Gimenez‐Roldan ; Nicolai & Lazzarino ; Zambrana Garcia et al ) have been described, but are usually responsive to treatment and rarely progressive (Stuerenburg et al ).…”
mentioning
confidence: 99%
“…One study reported the feasibility and safety of calcium supplementation treated only in symptomatic patients ("parathyroid stimulating"), and their management could also avoid unnecessary supplementation for most patients [12]. Some studies recommended preserving serum calcium at the low normal or mildly subnormal levels [4,11] because of the stimulation theory and to avoid side effects [4,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%